An improved method of recharge sources analysis and its application in an unconfined aquifer. (15th July 2021) - Huang, Yuming; Yan, Ni; Zheng, Xilai; Liu, Guanqun
Abstract: Groundwater recharge sources analysis, including identification of the recharge sources and calculation of the mixing ratios, is of great importance for hydrogeological research and water resources management. In this research, a new approach, multivariate mixing and mass-balance calculations (M3) model combined with MIX calculations (M3-MIX calculations), was proposed to overcome shortcomings and limitations of existing methods and to accurately describe aquifer systems with more than three groundwater sources and get more accurate mixing ratios. A synthetic case with random sources were applied to evaluate the effectiveness of M3-MIX calculations. The results of both mixing ratios and composition of recharge sources show that M3-MIX calculations is superior to traditional methods such as least squares, and is also superior to the results obtained by using M3 model or MIX calculations alone. The approach is then applied to analyze groundwater recharge sources of the Huangshui River groundwater reservoir, China. Three recharge sources were calculated based on M3-MIX calculations: brackish groundwater affected by seawater intrusion, atmospheric precipitation, and groundwater from upstream affected by agricultural activities. The mixing ratios of the three recharge sources are 3.3%, 19.3%, and 77.4%, respectively. In addition, ion concentrations deviate from the mixing line indicates that hydrochemical processes, such as mineral dissolution/precipitation and ion exchange processes, may occur in the study area. The results of this work indicate that M3-MIX calculations has the potential to provide the accurate understanding of groundwater recharge, and thus providing useful information for the exploitation, utilization, and protection of groundwater in unsaturated and saturated zones. Highlights: A novel analytical approach of M3 model combined with MIX calculations is proposed. The number of different types of recharge sources can be accurately determined. Mixing ratios of different recharges sources can be accurately calculated.